Workers’ Resistance across Time and Space: Presenting the Hub Global Labour Conflicts - Kösters, Rosa; Simpson, Catherine; Aurich, Jens (TSEG - The Low Countries Journal of Social and Economic History, 2023)
The Hub Global Labour Conflicts provides scholars, students, activists, and other interested audiences with historical and contemporary data on workers’ collective actions. The project is hosted by the International Institute of Social History in Amsterdam and aims to be a central resource for freely accessible labour conflict data from all over the world. By discussing how the Hub has evolved since its launch in 2015, this article reviews its accomplishments so far, its current limitations and potential areas for expansion. From this, we outline the ambition to make the Hub more global and thus even more strongly embedded within ongoing debates in global labour history. Thereby, we hope to introduce new audiences to the available data or enthuse you to contribute to the project.